Decolonial Provocations through Ecofeminist Pedagogies: Imagination in Times of Ecological Precarity - DIaz-Diaz, Claudia; Royo Letelier, Manuela (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
Climate change threatens communities’ livelihoods and significantly impacts how people envision their futures. In a context of ecological precarity, our study asked how women water and land defenders in Chile imagine the future; how their imaginations challenge patriarchal colonial systems of domination and how they foster alternative ways of living well together. To answer these questions, we investigated the pedagogical practices of an ecofeminist grassroots organization to understand how it operated as a knowledge-decolonizing laboratory where the imagination acted as a central tool. We discuss in this how decolonial and arts-based pedagogies can amalgamate sensorial awareness with relationships to place to challenge the rationality of knowledge production. We conclude by reflecting on how the feminist imagination comes into play to support the efforts of women as water and land protectors in Latin American contexts.